When Actin is Not Actin' Like It Should: A New Category of Distinct Primary Immunodeficiency Disorders - Evelien G.G. Sprenkeler; Steven D.S. Webbers; Taco W. Kuijpers (Karger Publishers, 2020)
An increasing number of primary immunodeficiencies (PIDs) have been identified over the last decade, which are caused by deleterious mutations in genes encoding for proteins involved in actin cytoskeleton regulation. These mutations primarily affect hematopoietic cells and lead to defective function of immune cells, such as impaired motility, signaling, proliferative capacity, and defective antimicrobial host defense. Here, we review several of these immunological "actinopathies" and cover both clinical aspects, as well as cellular mechanisms of these PIDs. We focus in particular on the effect of these mutations on human neutrophil function.